The corpus callosum and physical activity: An MRI volumetric study in stroke patients - Dagdeviren, Bekir; Demir, Caner Feyzi; Ogeturk, Murat; Yentur, Songul Baglan (Elsevier, 2025)
[Abstract Not Available]
ISN World Congress of Nephrology (WCN) -- FEB 06-09, 2025 -- New Delhi, INDIA